Penyuluhan Sistem Ternak Sehat dan Bersih sebagai Upaya Meningkatkan Kesehatan Ternak Ruminansia di Desa Gentan, Sukoharjo - Kristianto, Williams Tjong; Ferrando, Indigo; Febrianca, Ivory; Maura Tianska, Radine; Matilda Sianturi, Yemima; Fauzan Akmal, David; Annisa, Reni; Adelaide Vertin, Nadya; Pristihadi, Diah Nugrahani (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The Siternas program was implemented by the IPB University KKN-T Team in Gentan Village, Bendosari District, Sukoharjo Regency, as an effort to improve livestock health management among smallholder farmers. The program aimed to provide education and assistance to cattle, goat, and sheep farmers in order to establish a healthier, cleaner, and more productive livestock system. The implementation methods included coordination with the Department of Agriculture and Fisheries, initial observation, preparation of educational materials, and door-to-door extension activities combined with field practices. The program was carried out from July 21–23, 2025, across five hamlets, involving 26 farmers and 206 animals (47 cattle and 159 goats/sheep). The results indicated an increased understanding among farmers of the importance of deworming, proper housing management, and disease prevention. The program also distributed free Albendazole, conducted animal health checks, and demonstrated deworming methods. Challenges included language barriers, farmers’ limited availability, and substandard husbandry practices. Nevertheless, the program effectively raised awareness and encouraged farmers to adopt better health management practices. In conclusion, Siternas proved effective in enhancing farmers’ knowledge, skills, and motivation to maintain livestock health, while sustainability requires continuous mentoring, farmer health groups, and multi-sectoral collaboration.